2013
DOI: 10.1101/gad.206318.112
|View full text |Cite
|
Sign up to set email alerts
|

Spindle pole body-anchored Kar3 drives the nucleus along microtubules from another nucleus in preparation for nuclear fusion during yeast karyogamy

Abstract: Nuclear migration during yeast karyogamy, termed nuclear congression, is required to initiate nuclear fusion. Congression involves a specific regulation of the microtubule minus end-directed kinesin-14 motor Kar3 and a rearrangement of the cytoplasmic microtubule attachment sites at the spindle pole bodies (SPBs). However, how these elements interact to produce the forces necessary for nuclear migration is less clear. We used electron tomography, molecular genetics, quantitative imaging, and first principles m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 62 publications
3
27
0
Order By: Relevance
“…An intensively investigated karyogamic event is the fusion of two haploid nuclei during yeast mating, in which cytoskeleton-dependent nuclear migration, termed nuclear congression, and chaperon/endoplasmic reticulum (ER) protein-dependent nuclear fusion have been reported (Kurihara et al, 1994;Melloy et al, 2009;Tartakoff and Jaiswal, 2009;Gibeaux et al, 2013). Additionally, the cell cycle arrest and resumption induced by fertilization have been well studied using animal eggs (for review, see Kishimoto, 2003).…”
mentioning
confidence: 99%
“…An intensively investigated karyogamic event is the fusion of two haploid nuclei during yeast mating, in which cytoskeleton-dependent nuclear migration, termed nuclear congression, and chaperon/endoplasmic reticulum (ER) protein-dependent nuclear fusion have been reported (Kurihara et al, 1994;Melloy et al, 2009;Tartakoff and Jaiswal, 2009;Gibeaux et al, 2013). Additionally, the cell cycle arrest and resumption induced by fertilization have been well studied using animal eggs (for review, see Kishimoto, 2003).…”
mentioning
confidence: 99%
“…Strikingly, A. gossypii kar3 mutants were severely reduced in sporulation. In S. cerevisiae, Kar3 is required for nuclear congression to promote nuclear fusion during karyogamy (Gibeaux et al 2013). This therefore suggests that a key role for Kar3 in sporulation may be to promote karyogamy in A. gossypii.…”
Section: Functional Analysis Of Sporulation Specific Genesmentioning
confidence: 89%
“…Here, we analyzed the function of A. gossypii orthologs of S. cerevisiae KAR genes, which in S. cerevisiae either have a function both in mitosis and karyogamy or are specifically required for nuclear fusion during mating (Kurihara et al 1994). Kar3 plays a central role in pulling yeast nuclei together to prepare for karyogamy (Gibeaux et al 2013). A. gossypii kar3 mutants did not reduce growth speed of fast growing mature Ashbya hyphae and, therefore, Kar3 is not required for nuclear migration or positioning in vegetative hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…Early evidence showed that a microtubule cable extends from each SPB toward the other and that microtubule function is required for congression [147, 148]. Although cable shortening and lateral sliding had been thought to accomplish congression, investigations based on EM tomography show that congression results from the cables establishing lateral contact with the opposite SPB, where the minus-end directed motor, Kar3, exerts a pulling force [149]. It remains unclear whether the primary role of the cable is to bring the nuclei together or rather to cause the SPBs to contact each other.…”
Section: Karyogamymentioning
confidence: 99%